Design of Robust Stabilizing PI/PID Controller for time delay Interval Process Plants Using Particle Swarm Optimization (Advances in Systems Science and Applications, 2018)
Since most of the control systems operate under a large uncertainty, the study of robustness in stability has become vital in the presence of uncertainty. The largest uncertainty present in the control system causes degradation of system performance and destabilization. With a view to conquering the uncertainty, a novel approach for the design of robust PI/PID controller for the interval process plant is proposed in this paper. The proposed approach develops a robust PI/PID controller for the interval process plant with and without time delay based on necessary and sufficient conditions for stability of interval polynomial. Consequently, these conditions are used to derive a set of inequalities from the closed loop characteristic polynomial of an interval system in terms of controller parameters. Finally, these inequalities are solved to obtain controller parameters with the help of Particle Swarm Optimization (PSO). The proposed method has the advantage of having less computational complexity and easy to implement on a digital computer. The viability of the proposed methodology is illustrated through numerical examples of its successful implementation. The efficacy of the proposed methodology is also evaluated against the available approaches presented by Patre and Deore (2003), (2011) and the results were successfully implemented.